Evaluation of intervention strategy of thalassemia for couples of childbearing ages in Centre of Southern China. Issue 10 (7th September 2021) - Jiang, Fan; Zuo, Liandong; Li, Jian; Chen, Guilan; Tang, Xuewei; Zhou, Jianying; Qu, Yanxia; Li, Dongzhi; Liao, Can
Abstract: Background: To describe the free intervention strategy of thalassemia for childbearing couples in Guangzhou. Methods: Routine hematology examinations were conducted for 137, 222 couples. Among them, 37, 501 couples who had mean corpuscular volume (MCV) <82 fL or mean corpuscular hemoglobin <27 pg were elected for Hb analysis and the deletions of four common α‐thalassemia mutation. Reverse dot blot for common nondeletional α‐thalassemia and β‐thalassemia was selectively used. Three thousand twenty‐two couples randomly selected were offered all those tests as a control group. Sanger sequencing, multiplex ligation‐dependent probe amplification and next‐generation sequencing were used for rare thalassemia. High‐risk couples were offered prenatal diagnosis at 10–13 weeks' gestation based on informed consent. Results: The carrier rates of α‐, β‐, and αβ‐thalassemia and δβ thalassemia/deletional HPFH were 7.7%, 3.02%, 0.5% and 0.059% respectively. Of them, 1.37% were identified as at‐risk couples and 345 couples terminated the pregnancy. No severe α‐ and β‐thalassemia births were observed. In the control group, two β‐ thalassemia carriers and one case with −α 3.7 /αα QS were misdiagnosed, but all at‐risk couples were found, and we could save 1, 523, 774 ¥ using our strategy. The cut‐off points of 73.46 fL and 23.25 pg would be useful to find −α + /α T thalassemia. Conclusion: The intervention strategy was cost‐effective and offered reference in population thalassemia screening. Abstract : Flow‐chart for our thalassemia intervention strategy.